Correction: Corrigendum: Generation of stem cell-derived β-cells from patients with type 1 diabetes - Jeffrey R. Millman (Nature Portfolio, 2016)
Nature Communications 7: Article number: 11463 (2016); Published: 10 May 2016; Updated: 4 August 2016. The source of reagents for this Article was not fully acknowledged. The Acknowledgements should have included the following: ‘We thank Professors Robin Goland and Dieter Egli (https://www.cellhub.org) for patient fibroblasts.